Learning English and Chinese as foreign languages sociocultural and comparative perspectives - Wen-Chuan Lin 1966 (New Perspectives on Language and Education, 2019)
"This book compares English as a Foreign Language teaching in Taiwan with Chinese as a Foreign Language education in England and highlights how classroom activities are embedded within ethnic or social group cultures, family resources and school visions or goals, and it highlights the potential for a perpetuation of social inequality as a result"-- Provided by publisher.